Design of an Expert System for Determining Learning Styles (SIPATUGABEL) for Students at The Madrasah Tarbiyah Islamiyah (MTI) in Canduang - Sadar Martua Haholongan Sir; Supriadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Humans possess diverse potentials that are inherent from birth and must be nurtured to develop fully. These potentials can be developed in various ways, one of which is through learning. The learning process can help individuals develop their potential in accordance with their unique characteristics. Since every individual has different characteristics, students have diverse learning styles. It is crucial to consider learning styles in the learning process to ensure meaningful learning. The Merdeka Curriculum also includes several assessments, one of which is diagnostic assessment, which serves as the initial step a teacher takes to determine students’ baseline conditions both cognitive and non-cognitive. However, in implementing this diagnostic assessment at MTI Canduang, a challenge arises: the difficulty in accurately and quickly identifying students’ learning styles. Based on this problem, the researcher aims to design a web-based expert system for determining students’ learning styles using the Certainty Factor method, which can identify students’ learning styles in a valid, practical, and effective manner. The researcher employed the Research and Development (R&D) methodology to produce an expert system product, utilizing the Systems Development Life Cycle (SDLC) model with the Waterfall method, to develop an expert system for determining the learning styles of students at Madrasah Tarbiyah Islamiyah (MTI) Canduang. After the system was successfully designed, product testing was conducted. The results of the product testing, such as the system validity test, indicated that the system was valid, with an average score of 0.96 from the validator. The designed system was then deemed practical, achieving an average score of 0.93 from the practicality evaluator, and the designed system was deemed effective, achieving an average score of 0.56 from all respondents the fourth grade students of the MTI Canduang special class. Based on these test results, the designed expert system for determining learning styles was deemed valid, practical, and effective in determining learning styles quickly and accurately.